SENSHII - Diseño de joyería erótica para la estimulación de puntos erógenos en parejas (2024)
The erotic design represents a convergence between artistic creativity, technology and functionality. a p r a c t i c a, aimed at improving the sexual and emotional experience of couples. In a context where gender roles and cultural stigmas limit the full exploration of sexuality, the need arises for innovative products that allow for deeper and more satisfying intimacy. This degree work focuses on the development of erotic jewelry designed specifically for the stimulation of erogenous zones except the genital area, fusing the physical aspect of traditional jewelry with sensory technology (sensual tech). The proposal incorporates thermal and vibration elements, in order to provide an innovative physical stimulation experience.